Comparative Analysis of Selling Prices (CPO) in Indonesia Before and After the United States and China Trade War - Mayang Aprilianda; Chahayu Astina; Zefri Maulana (Jurnal Manajemen dan Keuangan, 2025)
The trade war between the United States and China occurred aniani4d because both countries implemented protectionist policies, which led to increased import tariffs on each other’s products. The purpose of this study is to analyze the differences in the selling price of Crude Palm Oil (CPO) in Indonesia before and after the trade war between the United States and China. This comparative study aims to examine two groups of variables across different periods. It employs a quantitative approach using secondary data, specifically the selling prices of CPO in Indonesia from January 2013 to December 2024. Data were collected through documentation and literature review. Based on the wilcoxon, the Sig. (2-tailed) value is 0.001, which is less than 0.05, indicating a significant difference in the selling price of CPO in Indonesia before and after the trade war.